'Seeing is believing': a qualitative approach to studying the use of cone beam computed tomography in endodontics in Sweden. (5th June 2019) - Mota de Almeida, F. J.; Flygare, L.; Knutsson, K.; Wolf, E.
Abstract: Aim: To gain insight into the decision processes of dentists when requesting a cone beam computed tomography (CBCT) examination in endodontic settings. Methodology: Fourteen dentists (eight female) 33–58 years of age (mean = 44) practising in Sweden were interviewed. Ten of the dentists were specialists in Endodontics. The absolute inclusion criterion was experience of referring patients for CBCT for endodontic reasons. The included dentists comprised a strategically selected diverse sample in terms of gender, age, work experience, educational background, location of practice, service affiliation and accessibility to CBCT. Data were obtained through semistructured interviews exposing the context of their last three self‐reported referrals. Dentists were encouraged to describe their experiences of the circumstances in their own words, aided by the interviewer's open‐ended questions. The interviews were audio‐recorded and transcribed verbatim. The text was analysed by qualitative content analysis. Results: The manifest content was organized into three categories that were defined as visualization as a desire, facilitating tough decisions and allocating responsibility. Conclusion: An overall theme (covering the latent content) was identified: A balance between clinical common sense and a 'better safe than sorry' attitude guides the use of CBCT in endodontic settings . Informants had high clinical standards, knowledge concerning radiation risks and good sense, which could compensate for their lack of knowledge of guidelines. The national radiation regulatory system was perceived to work as a slightly porous gatekeeper for over‐usage.